Communication and Collaboration in Library Technical Services: A Case Study of New York University in Abu Dhabi. Issue 2 (2nd July 2016) - Parrott, Justin
ABSTRACT: New York University Abu Dhabi Library has developed new strategies to increase efficiency in technical services processing between units based in New York and Abu Dhabi. This case study discusses the challenges specific to the international context and the methods used to overcome them, increase speed processing, and ultimately improve patron access to materials. A key factor in successful implementation was the strategic decision made by library administration to provide the newly-hired technical services librarian with three months of cross-training in New York before permanently moving to Abu Dhabi. A specific model of communication was put into action leading to the resolution of many problems and inefficiencies. In addition, a broader study of global communication tools was conducted and resulted in best practices for other library units within the university network. This case study outlines the background, communication processes and outcomes.